Transcending Educational Boundaries: Integration of Local Wisdom of the Ammatoa Indigenous Community in the Social Dynamics of High Schools - Rosmawati, Andi; Abunimye, Peter Ikpatem; Obuchi, Samuel M (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to determine the results of integrating local wisdom values of the Ammatoa indigenous community in social interactions in state high schools. Methodology: The research used is field research with a qualitative descriptive type. The approach used is a sociological approach. The data from this research comes from primary data and secondary data. The method uses observation, interviews and documentation, while the data collection techniques used are data reduction, data presentation and drawing conclusions. Main Findings: Based on the research results, it shows that the process of inheriting the values of local wisdom of the Ammatoa indigenous community in state high schools is greatly influenced by the efforts of teachers to take advantage of conditions to gain the trust of students, in this case trust provides an example of attitudes towards students, so that it can become a conscious effort that aims to pass on the values of local wisdom of the Ammatoa indigenous people. The inherited values include Pammopporang, Sipakatau, Sipakainga, and Tallasa Kamase-mase. Novelty/Originality of this study: The main breakthrough of this article lies in the interdisciplinary approach used to integrate the local wisdom of the Ammatoa Indigenous community into the social studies education curriculum.